Creating the Conditions for Free Time in the Debt Economy: On Stealing Time in and through Education - Wozniak, Jason (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
Philosophical discussions about leisure time often take place on an abstract level. But leisure time does not exist a priori to lived experience in concreate situations. Its existence, or the lack thereof, is often predicated on the material conditions of daily life. In this article the very real conditions of indebted life are the starting point for theoretical considerations on leisure time and education, and how education may or may not be an experience of leisure. Philosophers of education often leap to the emancipatory potential of conceptualizing education as a form of free time, before, or without, addressing the negations that stand in the way of this ideal becoming a reality. Conceptualizing education experience or schools as sites of leisure within the debt economy without first taking into consideration the ways in which debt negates leisure time leads to the production of education theories that only materialize into education realities on rare occasions. Thus, a central claim here is that education philosophers and practitioners must acknowledge the ways in which educational experiences are themselves conditioned, though not overdetermined, by the contemporary “debt economy.” Building on, with adaptations, theories of scholé, I aim to show the reader that despite the ways in which educational experience is shaped by debt, educational experience can suspend debt’s temporal force, providing momentary but much needed temporal respite from indebted life.